Metal‐Organic Frameworks Help Conducting Polymers Optimize the Efficiency of the Oxygen Reduction Reaction in Neutral Solutions. Issue 16 (20th May 2016) - Rafti, Matías; Marmisollé, Waldemar A.; Azzaroni, Omar
Abstract : The anchoring of an electro‐inactive metal‐organic framework (ZIF‐8 MOF) layer on a conducting polymer‐modified electrode enhances its electrocatalytic efficiency toward the oxygen reduction reaction in neutral solutions by a selective uptake and preconcentration of oxygen in the ZIF‐8 microporous matrix that ultimately acts as an oxygen reservoir in intimate contact with the electroactive material.